Evaluasi Kesuburan Tanah Sawah di Desa Detusoko Barat - Kaliktus Lanang Tobi; Henderikus Darwin Beja (Fakultas Pertanian, Universitas Nusa Nipa, 2026)
Soil fertility is an important factor determining rice productivity. This study aimed to evaluate soil chemical properties and soil fertility status of paddy fields in West Detusoko Village, Ende Regency. A descriptive method was employed using purposive sampling on rice fields cultivated with Inpari and Ciherang varieties. Laboratory analyses were conducted on several soil chemical properties, including soil pH, organic carbon, total nitrogen, available phosphorus, available potassium, cation exchange capacity (CEC), and base saturation. Data were analyzed using a matching method based on soil fertility criteria developed by the Indonesian Soil Research Center. The results indicated that soil pH ranged from slightly acidic to neutral (6.5–7.0), organic carbon and total nitrogen were categorized as moderate, available phosphorus was high to very high, available potassium was very low, cation exchange capacity was high, and base saturation was high to very high. The overall soil fertility status of the paddy fields was classified as moderate. The main limiting factors were low available potassium and moderate organic carbon content. Therefore, improving soil organic matter and applying balanced potassium fertilization are recommended to sustain rice productivity and soil quality in the study area.